Salt Sales Prediction Using the Moving Average Method (A Case Study of Madura-Indonesia Salt) - Syakur, Muhammad Ali; Negara, Yudha Dwi Putra; Rachmad, Aeri; Rochman, Eka Mala Sari (Elinvo (Electronics, Informatics, and Vocational Education), 2023)
Forecasting is a term used to forecast or predict the business that we run to see the direction in the future which uses historical data as the main reference. An appropriate strategy is needed to manage the production of salt raw materials properly, namely through sales forecasting. PT Budiono Madura Bangun Persada is a company engaged in salt processing with the brands "Anak pintar (AP)" and "Kapal Container (KC)" where the amount of production experiences uncertainty, namely an increase or decrease, this results in an uncertain amount of raw materials. This study aims to predict the exact amount of salt production in a certain period. The amount of data used is the period November 2020 - April 2021 as much as. The final result of this forecasting model is the best using predictions on day 6 for both AP salt and KC salt, with an MSE value of 290.71 for KC salt and an MSE value of 843.08 for AP salt